O Conselho Estadual do Povo de Terreiro: religiões afro-brasileiras e políticas públicas no Rio Grande do Sul - Marcelo Tadvald; Francisco Abrahão Gonzaga (Ciências Sociais Unisinos)
This work seeks to problematize the formulation and application of governmental public policies in recent years focused on the Afro-Gaucho religions, based on the formation context and recent actions of the State Council of the People of Terreiro (CPTERS) in the gaucho political scene. Following, we argue about some persecutory actions by local parliamentarians in recent years (2003, 2005, 2015), which sought to restrict liturgical practices that involve the free exercise of afro-religions in Rio Grande do Sul starting from a historical and present discussion and from references from the field of social studies of religion, thus seeking to situate the case of CPTERS within a larger framework of analysis involving themes such as ethnicity, racism and religious intolerance.